A qualitative study on the impact of COVID-19 on the behavior and attitudes of smokers and non-smokers in South Korea - Jieun Hwang; Hae-ryoung Chun; Eunsil Cheon (BMC, 2021)
Abstract Background The COVID-19 pandemic has affected all aspects of human society, including education, culture, and the economy, and has also introduced changes in people's health behaviors such as drinking alcohol, nutrition intake, and practicing healthy living. This study conducted qualitative research in the Korean context to examine the changes in the smoking behavior of smokers and secondhand smoke exposure of non-smokers during the COVID-19 pandemic. Methods Focus group interviews were conducted with 36 Korean participants (18 men and 18 women). The groups were composed of cigarette smokers, e-cigarette users, heated tobacco product users, and non-smokers. Results During the pandemic, it was found that there was an increase in the frequency of use, irrespective of the tobacco product, in users who refrained from social interaction and worked or studied from home. Users who continued to be socially active increased the amount used with each usage. Smokers showed a tendency to avoid smoking rooms and to smoke alone in places unoccupied by people. In addition, non-smokers' exposure to secondhand smoke did not decrease, but since non-smokers used masks, they reported more relief from the risk of exposure to secondhand smoke than before. Conclusions Despite smokers being a high-risk group for COVID-19, the risk did not result in smoking cessation among smokers. Therefore, policies and educational campaigns to raise awareness about the dangers of smoking and to encourage smoking cessation are needed in the future.